Frank Miller's Ronin - Miller, Frank 1957- (DC Comics, 2019)
"In this tale of a legendary warrior, the Ronin, a dishonored, masterless 13th Century samurai, is mystically given a second chance to avenge his master's death. But this time, it's in the 21st century. Frank Miller's post-apocalyptic graphic novel breakthrough is now released as a part of DC's prestigious new imprint of standalone graphic novels, DC Black Label. Suddenly finding himself reborn in a futuristic and corrupt 21st Century New York City, the samurai discovers he has one last chance to regain his honor: he must defeat the reincarnation of his master's killer, the ancient demon Agat. In a time and place foreign and unfathomable to him, the Ronin stands against his greatest enemy with his life and, more importantly, his soul at stake."--
"Original compilation, introduction, cover and bonus material published as RONIN: THE DELUXE EDITION. Originally published in single magazine form in RONIN 1-6.
Keywords: Samurai / Comic books, strips, etc; Rōnin / Comic books, strips, etc; Samouraï / Bandes dessinées; Rōnin / Bandes dessinées; COMICS & GRAPHIC NOVELS / Superheroes; Rōnin; Samurai; Comics (Graphic works); Graphic novels; Superhero comic books, strips, etc; Bandes dessinées; Comic